Value of lymph node biopsy in HIV / AIDS patient - Morelli Brum, Raúl; Larrosa, Juan; Barreiro, Claudia; Leites, Alejandra; Asti, Hugo (Cirugía del Uruguay, 1997)
Persistent and generalized lymphadenopathy (PGL) is part of the general clinical spectrum associated to HIV infection; however, an opportunistic infection, Kaposi's sarcoma ar non-Hodgkin's lymphoma can also determine the development of lymphadenopathy in sorne cases; and whereas in the case of PGL the histopathological study of a lymph nade would not be relevant, in the other cases a biopsy could be justified and be of interest from the point of view ot diagnosis, therapeutics and/or prognosis.